Gene expression mediates environmentally induced phenotypic plasticity in Chamaecyparis hodginsii seedlings - He, Tian-You; Zhu, Peng-Kai; Song, Cai-Ling; Wu, Min; Lin, Jian-Nan; Xu, Yan-Ping; Zhang, Jia-Lin; Zhang, Ying-Hui; Rong, Jun-Dong; Liu, Kai; Chen, Li-Guang; Zheng, Yu-Shan; et al. (Frontiers in Forests and Global Change, 2025)
In the context of climate change, assessing the adaptive potential of species and populations is crucial for developing effective conservation strategies. Changes in plant gene expression play a significant role in the adaptation process to climate change. This study aims to explore the adaptive responses of the conifer species Chamaecyparis hodginsii (the name has been revised from Fokienia hodginsii) to climate change and analyze the molecular-level reactions of these long-lived trees to climatic shifts. It seeks to understand their phenotypic responses to climate change, identify key environmental factors driving adaptive gene expression, and provide information for transplantation conservation strategies based on genetic adaptability. By conducting mixed-tissue RNA sequencing on samples from multiple provenances and employing redundancy analysis (RDA), weighted gene co-expression network analysis (WGCNA), and partial least squares path modeling (PLS-PM), the study assesses the impact of climatic variables on gene expression and phenotype. It identifies key gene groups associated with environmental responses and elucidates the complex relationships between environmental factors, functional gene groups, and phenotypic traits. The findings reveal that C. hodginsii adapts to environmental stresses by regulating specific gene activities related to morphological trait adjustments. Moreover, environmental factors such as the impact on tree architecture emphasize the importance of Precipitation Seasonality, Isothermality, and Precipitation of Driest Quarter for adapting to climate stresses. This research not only unveils the complex adaptive responses of C. hodginsii to climate change but also provides critical insights for the management and conservation of long-lived tree species facing climate change threats.